An extensive investigation on gamma shielding properties of PLA/Gd2O3 nanocomposites. (July 2023) - Niksarlıoğlu, Seçil; Akman, Ferdi; Pekdemir, Mustafa Ersin; Yalçın Kuzu, Serpil; Kaçal, Mustafa Recep; Yılmaz, Mücahit
Abstract: This paper presents the gamma shielding performance of Poly lactic acid (PLA) composites doped with 4%, 8%, 12%, and 16% Gd2 O3 to investigate the impact of dopant amount on gamma shielding with an energy of 241 Am (59.5 keV), 133 Ba (81.0, 276.4, 302.9, 356.0, 383.9 keV), 22 Na (511.0, 1274.5 keV), 137 Cs (661.7 keV), and 60 Co (1173.2, 1332.5 keV) sources. To characterize the radiation shielding properties of the samples, mass attenuation coefficient (μ/ρ), linear attenuation coefficient (μ), half-value layer (HVL), tenth-value layer (TVL), and effective atomic number (Zeff ) parameters were calculated and compared with the values computed by WinXCOM software. It is revealed that theoretical and experimental results are in agreement and the radiation protection efficiency was enhanced with the increase of the dopant amount. Radiation effects on the structure and thermal stability of the samples were also studied by Attenuated total Reflectance-Fourier transform infrared spectroscopy (ATR-FTIR) measurements and thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). The spectroscopy results showed a remarkable decrease in the absorbance value of the composites after gamma irradiation. Highlights: PLA/Gd2O3 polymer composites with different percentages were prepared. The radiation attenuation properties of these polymer composites were investigated. Shielding properties of Gd2O3 (%16) is better than the other samples. The absorbance signals in the ATR-IR spectra decreased after gamma irradiation. It was observed that Gd2O3 improved the shape memory property of nanocomposites.